Postgraduate training of healthcare professionals at Medical University – Sofia: financing and challenges - Vidin Kirkov; Mila Kirkova (Pharmacia)
After completing a six-year undergraduate medical program, during which young doctors acquire both theoretical knowledge and practical skills, they build the necessary foundation for independently addressing organizational, preventive, diagnostic, and other professional tasks. They then undergo postgraduate training to acquire a medical specialty in the Bulgarian healthcare system. This training involves mastering advanced theoretical knowledge and practical skills in a specific area of medical science and practice and concludes with a state examination. This article presents and analyzes the dynamics of financing postgraduate training of healthcare professionals in Bulgaria.